The Role of Law in AI-Based Business Ecosystems: A Contextualized Perspective from Islamic Law - Yoyo Arifardhani; Nur Hidayah Che Ahmat; Moh Mukri (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2025)
The rapid development of Artificial Intelligence (AI) has introduced complex legal challenges, particularly regarding regulation and compliance. This study examines the adequacy of Indonesia’s current legal framework in overseeing AI-based businesses and proposes an adaptive regulatory model informed by Islamic law. Using normative legal research and a qualitative approach, the study analyzes Indonesian legislation, Shariah legal principles, fatwās, academic literature, and comparative international regulations. Key regulatory gaps are identified in areas such as AI-based decision-making liability, algorithmic transparency, and data protection. These gaps are critically assessed through the lens of Maqāṣid al-Sharīʿah, including ḥifẓ al-ʿaql (protection of intellect), ḥifẓ al-māl (protection of wealth), and ḥifẓ al-nasl (protection of lineage and privacy), ensuring ethical alignment with Islamic values. To address these challenges, the research proposes a hybrid regulatory model combining principle-based and rule-based approaches, reinforced by risk-based standardization, certification schemes, and regulatory sandboxes. The “principle plus sandbox” model merges Shariah-based ethical norms with statutory regulation to support innovation while safeguarding public interest. Key contributions include: mapping Islamic legal objectives onto AI governance, designing a Shariah-compliant dispute resolution framework for AI-related business issues, and recommending the formation of a Shariah-informed AI regulatory authority in Indonesia. The study concludes that a balanced, adaptive legal framework—grounded in both legal certainty and Islamic ethical values—is essential for regulating AI in business contexts. This research contributes to developing more responsive, culturally rooted legal systems for AI governance in Muslim-majority countries